Effect of Calcium Channel Blockers on Platelet GPIIb-IIIa as a Calcium Channel in Liposomes: Comparison with Effects on the Intact Platelet - Rybak, Mary Ellen M; Renzulli, Lori A (Thrombosis and Haemostasis, 1992)
The platelet membrane glycoprotein IIb-IIIa complex is essential for platelet aggregation and functions as a fibrinogen receptor on the activated platelet. When incorporated into phospholipid vesicles, this glycoprotein complex can function as an apparent calcium channel which facilitates the transit of calcium across a phospholipid barrier. In order to further evaluate this calcium channel, the effect of calcium channel blockers of the dihydropyridine (nifedipine and nicardipine), arylalkylamine (verapamil) and benzothiazipine (diltiazem) classes were evaluated on GPIIb-Illa liposomes with encapsulated fura-2 (a fluorescent calcium indicator). Nicardipine, verapamil, and nifedipine significantly inhibited calcium influx into GPIIb-IIIa liposomes; however, this required 190 μM, 400 μM, and 140 μM drug, respectively. These concentrations are 10-1,000 fold greater than those clinically obtainable. In contrast, diltiazem at concentrations >220 μM and amiloride at concentrations >800 μM showed no inhibitory effects. When aspirinized platelets were activated with 30 μg/ml bovine fibrillar collagen, both nicardipine and diltiazem produced a decrease in both the initial rise and maximum cytoplasmic calcium concentration. Parallel experiments were performed to assess the effects of verapamil, nicardipine, and diltiazem on platelet aggregation in platelet rich plasma. Nicardipine, 190-380 μM, induced a prolongation of the lag phase, but no effect on the final degree of platelet aggregation to collagen. Similar inhibition of platelet aggregation was seen with diltiazem and verapamil although the effect of diltiazem was less pronounced particularly at higher concentrations of collagen. No effect was seen on aggregation with 32 μM ADP which is release independent, or on the primary wave of low dose ADP induced platelet aggregation. Verapamil (200 μM) and nicardipine (>190 μM) partially inhibited the secondary wave of 3.2 μM ADP aggregation. In contrast, diltiazem (400 μM) had limited effect on ADP induced aggregation. Similarly, both nicardipine and verapamil markedly inhibited platelet aggregation to 6 μM epinephrine; however, diltiazem had no effect. These data demonstrate that the GPIIb-IIIa calcium channel is selectively inhibited by different classes of calcium channel blockers. This inhibition requires concentrations much higher than that to inhibit classic voltage gated calcium channels and may be by a different mechanism. Further evaluation will determine whether this differential inhibition of the GPIIb-IIIa calcium channel is related to differences observed in platelet aggregation.